Tribological properties of auxetic and conventional polypropylene weft knitted fabrics - (:unkn) unknown (My University, 2010)
Purpose: The wear resistance and friction reducing properties of polymer fibres can be improved with negative Poisson's ratio behaviour. Poisson's ratio is defined as the ratio of transverse contraction strain to longitudinal extension strain in the direction of stretching force. Large number of materials have positive Poisson's ratio, however there are some materials which exhibit negative Poisson's ratio, they are termed auxetic materials. Auxetic materials present unique property that they expand in all directions when they are stretched and contract when compressed. This paper has highlighted, compared and discussed the variation between the modelling, theoretical and practical differences of auxetic materials wear behaviour. Design/methodology/approach: For the purpose of this work, auxetic and conventional fibres were produced by the melt spinning mechanism using extruder. The fibres physical properties were evaluated such as Poisson's ratio, fibre count, elongation, force and tenacity. Mono-filament fibres were used for fabrication of weft knitted fabrics; plain (1×1) structure was employed for knitting fabric. The wear resistance of the knitted fabrics were tested by using Nu-Martindale Abrasion and Pilling Tester and comparison were made. Findings: The abrasive wear test results demonstrated that the auxetic based weft knitted fabrics have superior wear behaviour than the conventional fibre based weft knitted fabrics. Practical implications: The experiment showed that the auxetic material is capable of sustaining large amount of abrasion compared to conventional fabric. Originality/value: The paper compare and discusse the variation between the modelling, theoretical and practical differences of auxetic materials wear behaviour. © Copyright by International OCSCO World Press.
Keywords: Abrasive wear; Auxetic materials; Poisson's ratio; Weft knitted fabric